Municipal solid waste incinerator residues - Sloot, Hans van der (Elsevier, 1997)
This final treatise and the summary report represent the culmination of the International Ash Working Group (IAWG) efforts from Feb. 1990 through July 1996; Includes bibliographical references (p. 779-834) and index.